High IL-8 plasma levels at baseline are predictive of poor overall survival in breast cancer patients receiving chemotherapy - Susanna Hilda Hutajulu; Yufi Kartika Astari; Dewi Kartikawati Paramita; Jihan Fadlila Gubiananda; Ado Pranawalingga; Meita Ucche; Lina Choridah; Lidya Meidania; Irianiwati Widodo; Suwardjo Suwardjo; Mardiah Suci Hardianti (BMC Research Notes)
Abstract Objective Our earlier work reported the association of inflammatory biomarker with a reduced breast cancer chemotherapy relative dose intensity (RDI) resulting in an unfavourable survival outcome. This current study aimed to assess the prognostic role of inflammatory biomarkers in patients with breast cancer, particularly Interleukin-8 (IL-8). Results This study included 168 breast cancer patients. The median follow-up was 24.3 (range 3–77) months. Kaplan-Meier and log-rank test showed that the 3-year overall survival (OS) in patients with high IL-8 plasma level (> 6.88pg/mL) were significantly lower than those with low level (≤ 6.88pg/mL) (59.6% vs. 76.4%, P = 0.049). Multivariate Cox regression analysis adjusted with stage and HER2 showed high IL-8 as prognostic factor for poor OS (HR 1.70, 95%CI [1.01–2.84], P = 0.044). Multivariate comparisons for disease-free survival (DFS) and progression-free survival (PFS) revealed none of the investigated inflammatory biomarkers having prognostic significance. More patients with older age and stage IV disease had a high IL-8 level than their counterparts (54 vs. 51 years, P = 0.020 and 61% vs. 39%, P = 0.012). High IL-8 level may serve as potential prognostic biomarker in the clinical setting in order to deliver more personalized care and strategy toward better outcomes.